2014
DOI: 10.4028/www.scientific.net/msf.805.61
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Functionality on Nanotubes of Ti-30Ta Alloy

Abstract: Recent studies have identified strong correlations between anodized metals and the production of highly biomimetic nanoscale topographies. These surfaces provide an interface of enhanced biocompatibility that exhibits a high degree of oxidation and surface energy. In this study, Human dermal fibroblasts (HDF, neonatal) were utilized to evaluate the biocompatibility of Ti-30Ta nanotubes after 1 day of culture. The anodization process was performed in an electrolyte solution containing HF (48%) and H2SO4 (98%) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The anodization process was performed according to our previous studies 27,30‐33 . Briefly, a dual electrode system with platinum and the Ti–30Ta alloy fixed 15 mm apart was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anodization process was performed according to our previous studies 27,30‐33 . Briefly, a dual electrode system with platinum and the Ti–30Ta alloy fixed 15 mm apart was used.…”
Section: Methodsmentioning
confidence: 99%
“…The anodization process was performed according to our previous studies. 27,[30][31][32][33] Briefly, a dual electrode system with platinum and the Ti-30Ta alloy fixed 15 mm apart was used. The electrolyte contained 0.2 M NH 4 F and glycerol and the voltage applied was 30 V for 6 hours.…”
Section: Ti-30ta Alloymentioning
confidence: 99%
“…Then, the alloy was cold -worked by a rotary swaging process and solubilized at 950 ºC for 2 hours followed by water cooling. The bars were cut into discs of 10 mm in diameter and 3 mm in thickness (Capellato, Smith, Popat, & Alves Claro, 2015). The samples were separated into group 1-Ti cp and group 2-Ti-30Ta.…”
Section: Samples Preparationmentioning
confidence: 99%
“…Wang et al observed that anodized tantalum surfaces possessing nanotubular oxide morphology promoted rabbit bone marrow mesenchymal stem cell adhesion and proliferation and in the meantime upregulated expression of osteogenic genes, including alkaline phosphatase, collagen-I, and osteocalcin (Wang et al, 2012). In addition, fibroblast cells were observed to spread more on anodized nanotubular Ti30Ta alloy and showed enhanced extracellular matrix production compared to nonanodized control samples (Capellato, Smith, Popat, & Alves Claro, 2014). In spite of the promising in vitro biological results obtained for nanotubular tantalum surfaces, no research was completed either on the biocompatibility or on the optimal size regime of the pores present on anodized nanoporous tantalum oxide surfaces.…”
Section: Introductionmentioning
confidence: 99%